A new species of Limnophyes Eaton, 1875 (Diptera: Chironomidae) from Llanos Orientales, Colombia - Dantas, Galileu P.s.; Ramos-Pastrana, Yardany; Hamada, Neusa (Zootaxa, 2022)
Limnophyes Eaton is a species-rich chironomid genus with more than 90 valid species distributed world-wide, of which nine species have been reported from the Neotropical region. In the present study, Limnophyes is recorded for the first time from Colombia based on Limnophyes llanero sp. n. from the Llanos ecoregion. The species can be distinguished from its congeners by having scattered lanceolate setae in the humeral and prescutellar area, epimeron II with six setae, posterior anepisternum II with one seta, and preepisternum without setae, and by having the apex of gonostylus expanded with a well-developed crista dorsalis.